Pengaruh Capital Intensity dan Kepemilikan Asing pada Agresivitas Pajak dengan Komisaris Independen Sebagai Pemoderasi - Amin Nur Azizah; Endry Purnomo; Siti Aisyah Nurrizqi Rahmadania (CV. ITTC INDONESIA, 2026)
Tax is the main source of state revenue and plays a crucial role in supporting national development. However, the implementation of the self-assessment system in Indonesia provides opportunities for companies to engage in tax aggressiveness through various tax planning strategies. This study aims to examine the effect of capital intensity and foreign ownership on tax aggressiveness with independent commissioners as a moderating variable. This research employs a quantitative approach using secondary data derived from the financial statements of consumer non-cyclicals sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2019–2023. Panel data regression analysis with interaction testing is used to analyze the moderating effect. Tax aggressiveness is measured using the Effective Tax Rate (ETR), capital intensity is measured by the proportion of fixed assets to total assets, and foreign ownership is measured by the percentage of shares owned by foreign investors. The results indicate that capital intensity and foreign ownership simultaneously affect tax aggressiveness. Partially, capital intensity and foreign ownership have an effect on tax aggressiveness. However, independent commissioners are not able to moderate the relationship between capital intensity and tax aggressiveness, nor between foreign ownership and tax aggressiveness. This study is expected to contribute to the development of tax accounting literature and provide insights for companies and policymakers in improving tax compliance.